'Don't Tell Me I'm Still on that Feckin' Island': Migration, Masculinity, British Television and Irish Identity in the Work of Graham Linehan. Issue 2 (1st June 2015) - Free, Marcus
Abstract : The article examines how, through such means as interviews and DVD commentaries, television situation comedy writer Graham Linehan has discursively elaborated a distinctly migrant masculine identity as an Irish writer in London. It highlights his stress on how the working environment of British broadcasting and the tutelage of senior British broadcasters facilitated the satirical vision of Ireland in Father Ted. It focuses on the gendering of his narrative of becoming in London and how his suggestion of interplays between specific autobiographical details and his dramatic work have fuelled his public profile as a migrant Irish writer.